2013
DOI: 10.1016/j.ibiod.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low concentrations of synthetic surfactants on polycyclic aromatic hydrocarbons (PAH) biodegradation

Abstract: The present study is focused on the effect of synthetic surfactants, at low concentration, on the kinetics of polycyclic aromatic hydrocarbons (PAH) biodegradation by Pseudomonas putida ATCC 17514 and addresses the specific issue of the effect of the surfactant on bacterial adhesion to PAH, which is believed to be an important mechanism for the uptake of hydrophobic compounds. For that purpose, three surfactants were tested, namely, the nonionic Tween 20, the anionic sodium dodecyl sulphate (SDS) and the catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Similar results were reported by Deschênes et al anthracene degradation in soil has not increased by SDS addition [16]. A decrease in anthracene degradation by P. putida was observed in the presence of SDS and CTAB [17]. Bautista et al study revealed that Tween 80 increases naphthalene and anthracene degradation by Pseudomonas sp., Enterobacter sp., Stenotrophomonas sp.…”
Section: Anthracene Biodegradation In the Presence Of Surfactantssupporting
confidence: 82%
See 1 more Smart Citation
“…Similar results were reported by Deschênes et al anthracene degradation in soil has not increased by SDS addition [16]. A decrease in anthracene degradation by P. putida was observed in the presence of SDS and CTAB [17]. Bautista et al study revealed that Tween 80 increases naphthalene and anthracene degradation by Pseudomonas sp., Enterobacter sp., Stenotrophomonas sp.…”
Section: Anthracene Biodegradation In the Presence Of Surfactantssupporting
confidence: 82%
“…So, it is very important to choose the correct combination between the micro-organisms, the PAHs substrate and surfactant molecule [17].…”
Section: Anthracene Biodegradation In the Presence Of Surfactantsmentioning
confidence: 99%
“…The ability to stimulate the biodegradation of PAHs by the use of surfactants has been confirmed by numerous researchers and is associated, e.g., with the mechanisms of increasing the bioavailability of hydrophobic compounds by their emulsification and/or solubilization, or altering the properties of the microorganisms cell surfaces (Ławniczak et al 2013). Rodrigues et al (2013) have reported that low concentrations of surfactants not only stimulated the decomposition of anthracene and fluoranthene but also indicated that the effect varied depending on the type and concentration of surfactant and the type of PAHs. An exceedingly high concentration or the wrong choice of surfactant can be toxic toward to microorganisms cells, resulting in a decrease of their number and, consequently, lower efficiency of the biodegradation process.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that, the hydrocarbon metabolism might occur in the microbes including halophilic hydrocarbonoclastic bacteria living in hypersaline conditions . The surfactants help to increase the adhesion efficiency with polycyclic aromatic hydrocarbons (PAH) to the biodegradation by Pseudomonas putida ATCC 17514 has been proved by Rodrigues et al …”
Section: Discussionmentioning
confidence: 98%